2014
DOI: 10.1177/155892501400900304
|View full text |Cite
|
Sign up to set email alerts
|

Improving Dimensional Stability of Cotton Knits through Resin Finishing

Abstract: The aim of this study was to compare the effectiveness of three different types of resin finishes for improving the dimensional stability of 100% cotton honeycombed pique knitted fabrics. After application of each resin at five different concentrations, it was found that the fabric shrinkage could be effectively controlled by using a suitable type and concentration of the resin. However, the cellulose crosslinking by the resin resulted in some loss in the fabric bursting strength. In a second set of experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…14 All of the data stayed within the shrinkage limit (±5%) for both lengthwise and widthwise shrinkage, probably because of its construction and heavy GSM. 15 Therefore, it was concluded that the effect of both lengthwise and widthwise shrinkage while changing the stitch length of base yarn, binding yarn, and fleecy yarn was within the acceptable limit.…”
Section: Effect Of Stitch Length On Shrinkage Propertiesmentioning
confidence: 97%
“…14 All of the data stayed within the shrinkage limit (±5%) for both lengthwise and widthwise shrinkage, probably because of its construction and heavy GSM. 15 Therefore, it was concluded that the effect of both lengthwise and widthwise shrinkage while changing the stitch length of base yarn, binding yarn, and fleecy yarn was within the acceptable limit.…”
Section: Effect Of Stitch Length On Shrinkage Propertiesmentioning
confidence: 97%
“…The 2D resin (Dimethylol dihydroxy ethylene urea, DMDHEU) is a typical resin of the nitrogen hydroxymethyl compound with low molecular weight, which has excellent properties in low formaldehyde emission, anti-wrinkle and anti-shrink mechanical properties, and stability, and is used to replace formaldehyde resin in the cotton fiber textile industry and wood modification [29][30][31][32][33]. Some researchers have carried out wood modification studies using 2D resin; the self-polymerization and cross-linking reaction of the 2D resin and wood compounds occurred within the cell wall, resulting in a permanent bulking of the cell wall and leading to a reduction in the swelling and shrinkage properties, thus with the dimensional stability considerably increased.…”
Section: Introductionmentioning
confidence: 99%
“…Fabric with improved dimensional stability can also be achieved by using elastomeric yarns. However, the product does not remain cost efficient due to high price elastane and additional heat setting process (Safdar et al, 2014;Senthilkumar, 2012). Shrinkage control with a mechanical compactor is also a successful application but it gives limited shrinkage control, which may not last after 4-5 washes (Mikuèionienë and Laureckienë, 2009).…”
Section: Introductionmentioning
confidence: 99%